Chickens as a simple system for scientific discovery: The example of the MHC. (July 2021) - Tregaskes, Clive A.; Kaufman, Jim
Highlights: Chickens played important roles in human societies for millennia, most recently for science. Chickens combine advantages of human and mouse systems for scientific discovery. Some important biological systems (like MHC) are simpler in chickens than typical mammals. Generalist and specialist MHC alleles were discovered in chickens, and extended to mammals. Abstract: Chickens have played many roles in human societies over thousands of years, most recently as an important model species for scientific discovery, particularly for embryology, virology and immunology. In the last few decades, biomedical models like mice have become the most important model organism for understanding the mechanisms of disease, but for the study of outbred populations, they have many limitations. Research on humans directly addresses many questions about disease, but frank experiments into mechanisms are limited by practicality and ethics. For research into all levels of disease simultaneously, chickens combine many of the advantages of humans and of mice, and could provide an independent, integrated and overarching system to validate and/or challenge the dogmas that have arisen from current biomedical research. Moreover, some important systems are simpler in chickens than in typical mammals. An example is the major histocompatibility complex (MHC) that encodes the classical MHC molecules, which play crucial roles in the innate and adaptive immune systems. Compared to the large and complex MHCs of typical mammals, the chicken MHC is compact and simple, with single dominantly-expressed MHC molecules that can determine the response to infectious pathogens. As a result, some fundamental principles have been easier to discover in chickens, with the importance of generalist and specialist MHC alleles being the latest example.